Planned caesarean section and neonatal morbidity - Bendezú Martínez, Andrés (2015)
OBJETIVE: To determine the morbidity of newborns scheduled cesarean. DESIGN: Retrospective, descriptive, comparative, transversal and analytical study. MATERIALS AND METHODS: 102 cases of newborns of pregnant women with cesarean deliveries scheduled treated at the Hospital of Obstetrics III Essalud "Felix Gutierrez Torrealva" of the city of Ica, in the period from January 1, 2000 Revised 31 December 2003. They were compared with a similar number of births vaginal delivery. RESULTS: During the study period, 3780 deliveries, 102 of which were attended by elective Caesarean section. Increased maternal age in 36.3% corresponded to the age group of 35-40 years old, 70 (70.6%) were married, 51.9% employed, 46.1% primigravid. The newborn Apgar was> = 7 in 96.7% of infants, there was no case of severe asphyxia; 58.8% were male, 70.6% with proper weight. 27.5% of cases of physiological jaundice, 17.7% with respiratory distress syndrome II and 7.8% with metabolic disorders, was found while in the control group were 6.9%, 4.9% and 3.9 % respectively; in the control group were 6.9 birth trauma and only 0.9% in the study group. CONCLUSIONS: There was relation between morbidity and the birth canal; disease risk was higher for infants born by elective Caesarean section.